2019
DOI: 10.1017/s0269889720000046
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of the glass ceiling in Italian academia: the case of economics

Abstract: ArgumentFollowing an international trend, Italy has reformed its university system, especially concerning methods and tools for research evaluation, which are increasingly focused on a number of bibliometric indexes. To study the effects of these changes, we analyze the changing profiles of economists who have won competitions for full professorship in the last few decades in the country. We concentrate on individual characteristics and on scientific production. We show that the identification of a univocal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…These works echo the findings of a larger literature, not based on network analysis, which highlights institutional concentration in economics (Hodgson & Rothman, 1999), that most, and sometimes virtually all, editorial board members of the so-called top journals graduated and work in a handful of economics departments in the United States; that these editors tend to stay in the role for very long, with possibly negative impact on the production and publication of innovative research (Heckman & Moktan, 2020); and more in general, the highly hierarchical and possibly oligopolistic nature of economics (Fourcade et al, 2015), and the widespread diffusion of scientific misbehaviour and professional malpractice (Le Maux et al, 2019) as well as discrimination (Corsi et al, 2019a(Corsi et al, , 2019b in academic economics as well as among students.…”
Section: The Literature On Citation Networkmentioning
confidence: 99%
“…These works echo the findings of a larger literature, not based on network analysis, which highlights institutional concentration in economics (Hodgson & Rothman, 1999), that most, and sometimes virtually all, editorial board members of the so-called top journals graduated and work in a handful of economics departments in the United States; that these editors tend to stay in the role for very long, with possibly negative impact on the production and publication of innovative research (Heckman & Moktan, 2020); and more in general, the highly hierarchical and possibly oligopolistic nature of economics (Fourcade et al, 2015), and the widespread diffusion of scientific misbehaviour and professional malpractice (Le Maux et al, 2019) as well as discrimination (Corsi et al, 2019a(Corsi et al, , 2019b in academic economics as well as among students.…”
Section: The Literature On Citation Networkmentioning
confidence: 99%
“…For example, Corsi et al . (2019b) noted that in economics in Italy, women are distributed in a pyramidal shape, with few full professors at the top, more associate professors in between, and the relative majority constituted by assistant professors at the base, whereas for men, the hierarchical structure is just the opposite, looking like an overturned pyramid. Moreover, evidence on economics allowed them to infer that bibliometric methods as well as peer review lead to a disadvantage for women.…”
Section: Swot Analysismentioning
confidence: 99%
“…Bibliometric analysis can help understand the structure and development of this research topic and its evolution [20]. There are some bibliometric research studies on different metaphors of gender inequalities [6,21], but we found very few bibliometric studies on the glass ceiling [21][22][23][24]. More specifically, Carpenter et al [24] conducted a bibliometric analysis to examine the academic trend of women in neurosurgery.…”
Section: Introductionmentioning
confidence: 98%